solve the following ODE: d^2(x) ------ = -ln(x)-1 dt^2 I've tried a couple of things and got this: d^2(x) ------ = -ln(x*e) dt^2 but couldn't solve it, your help is appriciated.
Follow Math Help Forum on Facebook and Google+
Originally Posted by zokomoko solve the following ODE: d^2(x) ------ = -ln(x)-1 dt^2 I've tried a couple of things and got this: d^2(x) ------ = -ln(x*e) dt^2 but couldn't solve it, your help is appriciated. The best I can do is to quadrature. Multiply your ODE by so and integrate giving so so (absorbing a 2 into c1)
View Tag Cloud